2003
DOI: 10.1021/cm030410x
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Wavelengths:  Synthesis and Photophysical Studies of Iridium Complexes and Their Applications in Organic Light Emitting Devices

Abstract: We have prepared and characterized a series of substituted 2-phenylbenzthiazole (4-CF3, 4-Me, 4-OMe, 4-F, 4-CN, and 3-F) ligands. The intermediate di-irrido and the six-coordinated mononuclear iridium(III) dopants of the above ligands have been synthesized and characterized. These complexes are thermally stable between 275 and 300 °C depending upon the types and volatility of substituents. They emit bright yellow to orange light. The peak emission wavelengths of the dopants can be finely tuned depending upon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
129
1
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(146 citation statements)
references
References 25 publications
15
129
1
1
Order By: Relevance
“…[11] As our understanding of structure-property relationships improves, we have found that DFT calculations provide an excellent method for modeling orbital configurations and extrapolating the energy of the lowest excited state. [11,14] These tech-A C H T U N G T R E N N U N G niques in conjunction with the other strategies presented herein have facilitated and expedited the design of useful materials for various optoelectronic, [4,39] analytical, [3,16] and photocatalytic applications. [18] Four areas in which the highly tunable nature of iridiumA C H T U N G T R E N N U N G (III) complexes have improved the performance of inorganic materials are discussed below.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…[11] As our understanding of structure-property relationships improves, we have found that DFT calculations provide an excellent method for modeling orbital configurations and extrapolating the energy of the lowest excited state. [11,14] These tech-A C H T U N G T R E N N U N G niques in conjunction with the other strategies presented herein have facilitated and expedited the design of useful materials for various optoelectronic, [4,39] analytical, [3,16] and photocatalytic applications. [18] Four areas in which the highly tunable nature of iridiumA C H T U N G T R E N N U N G (III) complexes have improved the performance of inorganic materials are discussed below.…”
Section: Introductionmentioning
confidence: 90%
“…Electron-withdrawing substituents tend to stabilize the HOMO by removing electron density from the metal, whereas donating groups have an inverse effect. [11,14,39,40] This relationship is convoluted by the fact that withdrawing groups may also lower the energy of the LUMO (i.e., increasing the electron affinity of the parent ligand). [14] Fortunately, the cyclometalating and ancillary ligands can be separately substituted with electron-withdrawing and A C H T U N G T R E N N U N G -donating groups in heteroleptic complexes, which enables deliberate control over the excited state.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In particular, ionic Ir complexes have emerged as promising chromophoric materials for lighting and display applications according to the reports of recent studies. [7][8][9][10][11][12][13][14][15] Inert metal electrodes that are resistant to oxidation in air can be used in these devices and the power consumptions of these devices are low.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] As one of the three primary colors for electrochemical properties. It was found that the excited state of the [Ir(piq) 2 (FbpyF)](PF 6 ) complex can be assigned to a mixed character of 3 LC (π N ∧ N Ǟπ* N ∧ N ), 3 MLCT, 3 LLCT (π C ∧ N Ǟπ* N ∧ N ), and 3 LC (π C ∧ N Ǟπ* C ∧ N ). In addition, the alkylfluorene-substituted complex, [Ir(piq) 2 (FbpyF)](PF 6 ), had relatively high quantum efficiency and good film-forming ability, and it was expected to be a good candidate for lighting and display applications.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the energy levels differ according to the position of the fluorine. 1,27 Their emission quantum yields were 0.36, 0.26, 0.36 and 0.28, respectively, as determined using Ir(ppy) 3 (0.40) used as the reference. 28 The respective HOMO energy levels of 1-4 were measured at -5.68, -5.86, -5.77 and -5.51 eV by low-energy photoelectron spectrometer (Riken-Keiki AC-2).…”
Section: Resultsmentioning
confidence: 97%